Relationship with Parents and Coping Strategies in Adolescents of Lima - Caycho, Tomás P. (2016)
This correlational and comparative study aims to determine the relationship between the perception of the relationship with parents and coping strategies in a sample of 320 students chosen through a non-probabilistic sampling of 156 men (48.75%) and 164 women (51.25%). To that end, information gathering instruments like the Children’s Report of Parental Behavior Inventory and Adolescent Coping Scale were used. The results suggest that there are statistically significant correlations between some dimensions of perception of the relationship with parents and coping strategies in the sample studied. Finally, with regard to the perception of parenting styles of both mother and father, we see no significant differences between men and women, except for the extreme autonomy of the father, in which men score higher than women. There were no some statistically significant differences in the analysis of coping strategies in the sample in relation to gender.